Fluidity and Education - Oberlechner, Manfred (International Dialogues on Education Journal, 2019)
This article shows why and how fluidity educates and is therefore of educational relevance for student teachers. If education sees the developmental process of the whole person, with regard to his or her “humanity”, as a life-long learning process, in which the individual expands his or her intellectual, cultural, creative and practical abilities and skills, then fluidity offers new perspectives for pedagogy. Education is then related to the subject’s exploration of inner and outer fluid realities, as processes of learning or socialization in an increasingly fluid postmodern society.